Czech Cubist Architecture - Jan Sedlák (Docomomo Journal, 2022)
At the turn of the twentieth century, the modernism of Otto Wagner, professor at the Academy of Fine Arts Vienna, was asserting itself at the forefront of architectural innovation of the Czech lands, then under Austro-Hungarian rule.